THE INFLUENCE OF CRYPTOCURRENCY MARKET ON THE FINANCIAL TRENDS OF THE PRESENT - Кавецький, Володимир (Socio-economic relations in the digital society, 2019)
The article is devoted to the study of the infl uence of the crypto market on the financial trends of the present. Different positions concerning the future of cryptocurrency and its interaction with the financial environment of influential and skilled persons of the financial world are considered. The current investment environment and the connection of cryptocurrency with it are analyzed. The use of cryptocurrency and blockchain technologies in economic relations has been worked out. The analysis of the possible application of cryptocurrency in the banking sector and the Internet of things was made. The tendencies and prospects of development of cryptocurrency are investigated. It was found out that the cryptocurrency market, due to its young age, is experiencing a negative squeal from speculators. However, the potential for cryptocurrency use is so obvious that it should at present be regarded as a fi nancial instrument that is capable of solving some pressing problems of the modern financial system. It is determined that cryptocurrency has a brilliant future, and there are wide opportunities for leading countries in this field. So, the pace of innovation is accelerating all the time, so the need to keep up the whole time is all the more important. Cryptocurrency is considered as a method of investing, paying for purchases, using electronic devices, etc. Obviously, now it’s impossible to ignore the cryptocurrency boom. Since, as the bitcoin and other litecoins, and with them, companies that are their supporters, which emphasize their connection with the crypto industry, are beginning to invest in the real economy, and we see how cryptocurrency begins to affect the real economy. So, it was found that cryptocurrency penetrates deeply into the global fi nancial space, and the use of digital currencies has minimal risks for financial stability and the monetary system of the state.